Carriage of Carbapenem-Resistant Enterobacterales in Adult Patients Admitted to a University Hospital in Italy - Pamela Barbadoro; Daniela Bencardino; Elisa Carloni; Enrica Omiccioli; Elisa Ponzio; Rebecca Micheletti; Giorgia Acquaviva; Aurora Luciani; Annamaria Masucci; Antonella Pocognoli; Francesca Orecchioni; Marcello Mario D'Errico; et al. (MDPI AG, 2021)
The emerging spread of carbapenemase-producing Enterobacterales (CPE) strains, in particular, Klebsiella pneumoniae and Escherichia coli, has become a significant threat to hospitalized patients. Carbapenemase genes are frequently located on plasmids than can be exchanged among clonal strains, increasing the antibiotic resistance rate. The aim of this study was to determine the prevalence of CPE in patients upon their admission and to analyze selected associated factors. An investigation of the antibiotic resistance and genetic features of circulating CPE was carried out. Phenotypic tests and molecular typing were performed on 48 carbapenemase-producing strains of K. pneumoniae and E. coli collected from rectal swabs of adult patients. Carbapenem-resistance was confirmed by PCR detection of resistance genes. All strains were analyzed by PCR-based replicon typing (PBRT) and multilocus sequence typing (MLST) was performed on a representative isolate of each PBRT profile. More than 50% of the strains were found to be multidrug-resistant, and the blaKPC gene was detected in all the isolates with the exception of an E. coli strain. A multireplicon status was observed, and the most prevalent profile was FIIK, FIB KQ (33%). MLST analysis revealed the prevalence of sequence type 512 (ST512). This study highlights the importance of screening patients upon their admission to limit the spread of CRE in hospitals.